Emergency management of 2019 novel coronavirus: implications for the dermatology department. (1st June 2020) - Tao, J.; Song, Z.; Yang, L.; Huang, C.; Feng, A.; Man, X.
Summary: Since cases first emerged in December 2019, COVID‐19 (a type of coronavirus) has rapidly become pandemic. This fast‐tracked paper (published quickly) from China on COVID‐19 is written by dermatologists at the epicentre of the outbreak in Wuhan. Dermatology clinic staff may be at risk because protective equipment is not routinely available, and skin lesions might possibly transmit the virus indirectly. These authors suggest preventive measures based on experience in this and previous coronavirus outbreaks. Online consultation for non‐urgent patients reduces the numbers of patients attending clinics. Nurse‐led triage, to identify patients with possible COVID‐19, at the entrances of hospital and skin clinics directs patients with a cough or fever to a specific COVID‐19 area and a dermatologist is consulted if the fever might be related to skin disease. Clinic staff wear N95 masks and observe hand hygiene during consultations. Patients are admitted to a ward only if routine blood tests and chest CT scans exclude COVID‐19. Triage will not detect patients who are showing no symptoms but who are developing the disease, so the hospital should provide an on‐call expert team to discuss inpatients suspected or diagnosed with COVID‐19 and refer them to radiology, respiratory or intensive care colleagues as required. Confirmed cases are managed following local policies. Skin disorders in COVID‐19 inpatients can usually be managed remotely using photographs, email and teleconferencing. If necessary a multidisciplinary team (a team of medical staff from different specialties) can meet in the clean area of the isolation ward. If the dermatologist must see the patient, all records should be provided in advance to minimise exposure time. With these precautions, as of 20th February 2020 no infected patients were detected in the Wuhan Dermatology Department. This is a summary of the study: Emergency management for preventing and controlling nosocomial infection of 2019 novel coronavirus: implications for the dermatology department